Is health politically irrelevant? experimental evidence during a global pandemic - Acharya, A; Gerring, J; Reeves, A (BMJ Publishing Group, 2020)
Objectives: Little is known about how health issues affect voting behaviour. The Covid-19 pandemic offers a unique opportunity to examine this interplay.